Effectiveness of brentuximab vedotin monotherapy in relapsed or refractory Hodgkin lymphoma: a systematic review and meta-analysis. Issue 14 (6th December 2021) - Plattel, Wouter J.; Bergamasco, Aurore; Trinchese, Fabrizio; Gavini, François; Bent-Ennakhil, Nawal; Zomas, Athanasios; Castillon, Genaro; Arredondo-Bisono, Teigna; Cristarella, Tiffany; Moride, Yola; von Tresckow, Bastian
Abstract: This systematic review and meta-analysis aimed to determine the effectiveness of brentuximab vedotin (BV) in relapsed/refractory classical Hodgkin lymphoma (R/R cHL) in the clinical practice setting using most recent results. A total of 32 observational studies reporting on treatment patterns, overall response rate (ORR), complete response (CR) rate, progression-free survival (PFS), overall survival (OS), and adverse events were found. After four cycles, a random-effect model yielded pooled ORR and CR rates of 62.6% (95% confidence interval (CI): 56.0–68.9; I 2 = 9.7%) and 32.9% (95% CI, 20.8–46.3, I 2 = 64.8%), respectively. Regarding survival, 1-year, 2-year, and 5-year PFS ranged from 52.1% to 63.2%, 45.2% to 56.2%, and 31.9% to 33.0%, respectively. OS rates were 68.2–82.7%, 58.0–81.9%, and 58.0–62.0%, respectively. Most common adverse events were hematological toxicities (neutropenia: 13.3–23%, anemia: 8.8–39.0%, and thrombocytopenia: 4–4.6%), and grade ≥3 peripheral neuropathy (3.3–7.3%). This study supports the effectiveness and safety of BV in R/R cHL patients in the real-world setting.